Detection of the iroN gene in strains of avian pathogenic Escherichia coli in ducks at the Surabaya live market - Kendek, Irfan Alias; Effendi, Mustofa Helmi; Wibisono, Freshinta Jellia; Putri, Mariana Febrilianti Resilinda; Abidin, Zainul; Naseh, Naseh; Rehman, Saifur; Khairullah, Aswin Rafif; Yanestria, Sheila Marty; Pratama, Bima Putra; Kurniasih, Dea Anita Ariani; Ahmad, Riza Zainuddin; Tang, John Yew Huat; Kurniawan, Muhammad ‘Ahdi; Dameanti, Fidi Nur Aini Eka Puji (Jurnal Medik Veteriner, 2026)
Escherichia coli normally inhabits the intestinal tract of poultry as a commensal organism; however, specific strains such as avian pathogenic E. coli (APEC) may become opportunistic pathogens responsible for colibacillosis in birds. The inappropriate use of antibiotics can increase antimicrobial resistance, which may impact public health. This study aimed to detect the presence of the iroN virulence gene specifically in multidrug-resistant (MDR) E. coli isolates associated with APEC obtained from duck cloacal swabs collected at live markets in Surabaya. This study was designed as a descriptive cross-sectional survey, and the results are presented as prevalence proportions without inferential or correlation statistical testing, as iroN detection was performed exclusively on MDR isolates. Samples were collected from five live markets in Surabaya and cultured on MacConkey agar (MCA). E. coli was identified morphologically through Gram staining and biochemically using Triple Sugar Iron Agar (TSIA), Sulfide Indole Motility (SIM), Simmons Citrate Agar (SCA), indole, and methyl red–Voges–Proskauer (MR–VP) tests. Antimicrobial susceptibility testing was performed on all confirmed E. coli isolates (n = 120), and PCR analysis of the iroN gene was subsequently conducted only on MDR isolates (n = 14). The identification rate of E. coli in this study was 83.3% (120/144). Resistance to erythromycin was 81.7% (98/120), which likely reflects the intrinsic resistance of Gram-negative bacteria to macrolides rather than acquired antimicrobial resistance. This was followed by resistance to gentamicin at 19.2% (23/120), ciprofloxacin at 14.2% (17/120), aztreonam at 3.3% (4/120), and chloramphenicol at 2.5% (3/120). The prevalence of multidrug resistance (MDR) was 11.6% (14/120). Among these MDR isolates, 42.8% (6/14) were positive for the iroN virulence gene. No statistical association between MDR status and iroN carriage was assessed because non-MDR isolates were not screened for iroN. These findings provide baseline descriptive data on MDR and iroN-positive E. coli in traditional markets in Surabaya based on a limited panel of representative antimicrobial classes, without inferring specific resistance mechanisms such as extended-spectrum β-lactamase (ESBL) production.